Respuesta :

Answer:

b. y=-2x+3

Step-by-step explanation:

find slope by getting any 2 points form the graph

(0,3) (1,1)

m = (y2-y1) / (x2-x1)

m = (1-3) / (1-0) = -2 it means by moving one unit right you need to move 2 unit down

note that it does not matter which points you chose to be second or first

then use slope point equation again it does not matter which point from the slope you use

y - y1 = m ( x - x1 )

y - 3 = -2 ( x - 0)

y = -2x +3

a) 2x+3

Step-by-step explanation:

The line passes throught the point (1;1) and (0;3)

gradient(m) =change in y ÷ change in x

=y1-y2 ÷x1-x2

=1-3 ÷ 1-0

=-2

therefore m is -2.

y-y1=m(x-x1)

y-1=-2(x-1)

y=2x+2+1

y=2x+3

ACCESS MORE